Implementation of Forest Certification in Brazil, Spain And Portugal: An Analytic Hierarchy Process (AHP) Application. (1st March 2019) - Alvesa, R.R.; Fraj-Andrésb, E.; Rojo-Alborecac, A.; Graciolia, C.R.
Forest certification is an important mechanism for the legitimation of environmental practices in the sustainable forest management. Its basis are the forest management standards, which represent the guidelines for defining sustainable forest management through a hierarchical structure (principles, criteria and indicators), which includes social, environmental and economic issues. The main certification systems in the world, FSC and PEFC, have adopted this structure in their forest management standards. This work aims to evaluate the perception of experts in Brazil, Spain and Portugal regarding the level of difficulty to implement forest certification applying the Analytic Hierarchy Process (AHP). The principal results indicated that, in general, the principles related to environmental aspects are considered the most complicated to comply, the social aspects are much more difficult to achieve in the case of Brazil, and the economic aspects are not considered as an important problem in any of the three countries.